(untitled) (European Journal of Formal Sciences and Engineering, 2024)
The aviation industry faces mounting pressure to reduce fuel consumption, emissions, and noise pollution while maintaining or improving performance. This comprehensive review examines various methods and emerging technologies for enhancing conventional turbofan engine efficiency. The study analyzes multiple approaches, including advanced bypass ratio optimization, innovative gearbox systems, novel composite materials, and introduces a new twin-fan concept. Through systematic analysis of current literature and industry developments, this research demonstrates that significant improvements in engine efficiency can be achieved through the integration of multiple enhancement methods. The study particularly focuses on the relationships between bypass ratio modification, gearbox implementation, material selection, and their combined effects on fuel consumption, emissions, and noise reduction. The proposed twin-fan concept presents a novel approach to increasing air inlet efficiency while maintaining operational stability. Experimental data and theoretical analyses suggest that these combined approaches could potentially yield 15-20% improvement in fuel efficiency compared to conventional designs, while simultaneously reducing noise levels by 8-10 decibels.